MRI/SPECT/Fluorescent Tri‐Modal Probe for Evaluating the Homing and Therapeutic Efficacy of Transplanted Mesenchymal Stem Cells in a Rat Ischemic Stroke Model. (17th December 2014) - Tang, Yaohui; Zhang, Chunfu; Wang, Jixian; Lin, Xiaojie; Zhang, Lu; Yang, Yi; Wang, Yongting; Zhang, Zhijun; Bulte, Jeff W. M.; Yang, Guo‐Yuan
Abstract : Quantitatively tracking engraftment of intracerebrally or intravenously transplanted stem cells and evaluating their concomitant therapeutic efficacy for stroke has been a challenge in the field of stem cell therapy. In this study, first, an MRI/SPECT/fluorescent tri‐modal probe ( 125 I‐fSiO4@SPIOs) is synthesized for quantitatively tracking mesenchymal stem cells (MSCs) transplanted intracerebrally or intravenously into stroke rats, and then the therapeutic efficacy of MSCs delivered by both routes and the possible mechanism of the therapy are evaluated. It is demonstrated that (125) I‐fSiO4@SPIOs have high efficiency for labeling MSCs without affecting their viability, differentiation, and proliferation capacity, and found that 35% of intracerebrally injected MSCs migrate along the corpus callosum to the lesion area, while 90% of intravenously injected MSCs remain trapped in the lung at 14 days after MSC transplantation. However, neurobehavioral outcomes are significantly improved in both transplantation groups, which are accompanied by increases of vascular endothelial growth factor, basic fibroblast growth factor, and tissue inhibitor of metalloproteinases‐3 in blood, lung, and brain tissue ( p < 0.05). The study demonstrates that 125 I‐fSiO4@SPIOs are robust probe for long‐term tracking of MSCs in the treatment of ischemic brain and MSCs delivered via both routes improve neurobehavioral outcomes in ischemic rats. Abstract : An MRI/SPECT/fluorescent tri‐modal probe is synthesized and used for labeling and quantitive tracking of mesenchymal stem cells transplanted intracerebrally or intravenously into stroked rats. About 35% of intracerebrally implanted mesenchymal stem cells migrate from the injection sites and accumulate in the lesion area. While mesenchymal stem cells injected intravenously are primarily trapped in the lung, both injection routes improve brain function.